Examination of the relation between S/EUROP carcass classification for sheep and certain slaughter parameters - Mezőszentgyörgyi, Dávid; Toldi, Gyula; Lengyel, Attila; Andrássy Baka, Gabriella (Acta Agraria Kaposváriensis, 1999)
In this study the authors compared the slaughtering characteristics of Hungarian Merino and lie de France sheep with their S/EUROP classification results. They established that the classification system presently used is well-suited for application in the evaluation of carcass commercial value, but at the same time also point out errors in this system. The development and introduction of a new, more objective method is recommended.